The overexpression of actin related protein 2/3 complex subunit 1B(ARPC1B) promotes the ovarian cancer progression via activation of the Wnt/β-catenin signaling pathway - Huang, Junning; Zhou, Haiqin; Tan, Caichun; Mo, Shien; Liu, Tingji; Kuang, Yan (Frontiers in Immunology, 2023)
Introduction: Ovarian cancer is one of the most fatal malignancies of the female reproductive system. The purpose of this study is to explore the mechanism of Actin Related Protein 2/3 Complex Subunit 1B(ARPC1B) in the progression of ovarian cancer. Methods: The expressions and prognostic value of ARPC1B in ovarian cancer were identified using the GEPIA database and the Kaplan-Meier Plotter database. The expression of ARPC1B was manipulated to evaluate its impact on the malignant phenotypes of ovarian cancer . The cell proliferation ability was analyzed through CCK-8 assay and clone formation assay. The cell migration and invasion capacity was evaluated through wound healing assay and transwell assay. Mice xenografts were conducted to measure the effects of ARPC1B on tumor development in vivo. Results: Our data suggested that ARPC1B was overexpressed in ovarian cancer, which was correlated with a poorer survival compared to low mRNA expression of ARPC1B in ovarian cancer patients. The overexpression of ARPC1B promoted cell proliferation, migration, and invasion of ovarian cancer cells. Conversely, the knockdown of ARPC1B resulted in the opposite effect. Additionally, ARPC1B expression could activate Wnt/β-catenin signaling pathway. The administration of the β-catenin inhibitor XAV-939 abolished the promotion of cell proliferation, migration, and invasion activities induced by ARPC1B overexpression in vitro. Conclusions: ARPC1B was overexpressed in ovarian cancer and was correlated with poor prognosis. ARPC1B promoted ovarian cancer progression through activation of Wnt/β-catenin Signaling Pathway.